Imaging Impulsivity in Parkinson's Disease and the Contribution of the Subthalamic Nucleus. (5th June 2011) - Ray, Nicola; Antonelli, Francesca; Strafella, Antonio P.
Abstract : Taking risks is a natural human response, but, in some, risk taking is compulsive and may be detrimental. The subthalamic nucleus (STN) is thought to play a large role in our ability to inhibit responses. Differences between individuals' ability to inhibit inappropriate responses may underlie both the normal variation in trait impulsivity in the healthy population, as well as the pathological compulsions experienced by those with impulse control disorders (ICDs). Thus, we review the role of the STN in response inhibition, with a particular focus on studies employing imaging methodology. We also review the latest evidence that disruption of the function of the STN by deep brain stimulation in patients with Parkinson's disease can increase impulsivity.